PERANAN KEBIASAAN BERBELANJA YANG MEMEDIASI PENGARUH PERSEPSI HARGA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS ROKOK MARLBORO DI BANDA ACEH) - Nailil Muna; Sulaiman Sulaiman (Jurnal Manajemen Inovasi, 2020)
This study aims to examine the effect of price perceptions and brand image on purchasing decisions where the shopping habits variable is mediated in the relationship. Data was collected from 100 people in Banda Aceh City using the Purposive Sampling method. The results showed that the perception of prices did not significantly influence shopping habits and the decision to purchase Marlboro brand cigarettes in the people of Banda Aceh City. Brand Image has a significant influence on shopping habits and the decision to purchase Marlboro brand cigarettes in the people of Banda Aceh City. Shopping habits are proven to mediate partially on the relationship brand image of purchasing decisions.